Application of clustering algorithm for analysis of Student Academic Performance - Seetharam Nagesh, A; Satyamurty, VS (International Journal of Computer Sciences and Engineering, 2025)
The analysis of the Student academic performance in educational institutions is a crucial task to make managerial decisions and to impart quality education. The data pertaining to the educational institutions is increasing rapidly. Mining these large volumes of the data will help the management to make academia decisions. Predicting the academic performance of the student at an early stage of their course will help the academia to identify the merit students and also to put more efforts in developing remedial programs for the weaker students to improve their performance. In this paper, we applied k-means clustering algorithm for analysing the students result data and predicting the students’ performance.